PENGEMBANGAN LEMBAR KERJA SISWA BERORIENTASI KETERAMPILAN PROSES DALAM PEMBELAJARAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN SISTEM PENCERNAAN MANUSIA - Hasbullah Hasbullah (Bioedukasi: Jurnal Pendidikan Biologi FKIP UM Metro, 2016)
The purpose of this study is to optimize the use of the Student Worksheet Worksheet student develops process-oriented skills, do Design Student Worksheet that can, measure student learning outcomes, do Design Student Worksheet on the subject of the Human Digestive System. For learners, learning must shift from "Notified" to "Actively seek out". The product specifications are expected in this study resulted in the Student Worksheet process-oriented skills that have the right procedures, adherence to learning the which includes initial, core and closing activity. Sheets Readability students a clear and operational notes the existence of multiple Interpretations by students, can measure cognitive learning outcomes. In this study, using research and development is commonly known Research & Development (R & D). Strategy to develop an educational product by Borg and Gall (1930) Referred to as research and development. Constructs validation by experts / specialists namely sheets Validation for experts in the form of an expert assessment of the various components and materials contained in LKS and observation Instrument Science Process Skills.